A Descriptive Cross-Sectional Study of Manipulative Dexterity on Different Subtypes of Multiple Sclerosis - Elisabet Huertas-Hoyas; Nuria Máximo-Bocanegra; Carlos Diaz-Toro; Raquel Montes-Diez; Jorge Pérez-Corrales; Patricia Sánchez-Herrera-Baeza; Rosa Mª Martínez-Piédrola; Cristina García-Bravo; Carlos Sánchez-Camarero; Marta Pérez-de-Heredia-Torres (Occupational Therapy International)
Background. Manipulative dexterity impairments affect 76% of individuals with multiple sclerosis (MS). Patients with MS can experience reduced skill when performing both basic activities of daily living and instrumental activities of daily living. Many studies consider that physical rehabilitation leads to a decrease in the level of disability, especially at the mild and moderate stages of the disease. However, most studies fail to distinguish between the different MS subtypes. Purpose. Our aims were (1) to describe the manipulative skills of people according to the different subtypes of MS, (2) to analyze the correlation between dexterity and self-perception variables, and (3) to identify possible predictors of functionality. Study Design. A descriptive cross-sectional study. Methods. 30 individuals with MS. The measurement tools used were the ABILHAND, the Purdue Pegboard Test (PPT), the Nine-Hole Peg Test, and the Box and Block Test. Results. All subtypes of MS obtained lower scores for manipulative dexterity compared to normal skill levels, with individuals with primary progressive MS displaying the lowest values. However, the analysis of differences between the different subtypes did not reveal statistically significant intragroup differences. In addition, differences were found regarding the effect size of practically all the variables analyzed for both manipulative dexterity (PPT, NHPT, and BBT) and the self-perception of ADLs (ABILHAND), for which high values (dr=0.72) and very high values (dr=1.46) were obtained. Conclusions. Although no significant differences were found between the different types of MS, the assessment of manual dexterity and perceived efficacy of daily activities must be considered as prognostic factors in the progression of the disease. These findings may help support further research on targeted interventions to improve dexterity deficiencies, as well as promote an improved quality of therapeutic interventions.